Editorial - Corene de Wet (Perspectives in Education, 2011)
From text: This issue of Perspectives in Education has a fascinating collection of national and international contributions. All the contributions deal with the field of education and provide a collection  of perspectives on important issues in the science of education, including the transformation of higher education institutions, complexities in the teaching of history, language-in-education,  assessment, and the misalignment in the South African education pathway system.